Immunological and Physiological Differences Between Layer- and Broiler Chickens after Concurrent Intratracheal Administration of Lipopolysaccharide and Human Serum Albumin - Parmentier, H.K.; Reilingh, G. de Vries; Freke, P.; Koopmanschap, R.E.; Lammers, A. (International Journal of Poultry Science, 2010)
Layers and broilers were concurrently intratracheally challenged with 0.5 mg Lipopolysaccharide (LPS) and 0.1 mg Human Serum Albumin (HuSA) at 3 weeks of age. Specific total and isotype-specific (IgM, IgG, IgA) Antibody (Ab) responses to HuSA during 3 weeks following immunization, cellular in vitro mitogen responses to Concanavalin A (Con A) and specific cellular responses in vitro to different dosages of HuSA, blood serotonin (5-HT) levels, plasma Corticosterone (CORT) levels at 6 weeks of age and ex vivo nitric oxide (NO) production in the presence of LPS, respectively, were measured in all birds. Higher in vitro cellular responses to HuSA, but not Con A, were found in the broilers than in the layers. Also higher total, IgM and IgG antibody responses to HuSA were found in the broilers. Higher ex vivo NO production was found in the layers. A heavier spleen weight was found in the broilers, but relative spleen weight was higher in the layers. The broilers grew much heavier and also maintained a higher growth during the first 24 and 48 h after i.t. challenge with LPS and HuSA. No breed effect was found for body temperature responses after i.t. challenge. Blood 5-HT levels and plasma CORT levels were significantly higher in the layers. Number and type of significant correlations between 5-HT levels, cachectin response to LPS, antibody levels and cellular immunity differed between breeds. Our data suggest comparable immune responses to i.t. HuSA challenge in broilers and layers of similar age and confirm the earlier reported higher humoral immune response in broilers. On the other hand, the cachectin response to LPS differed between broilers and layers. Our results do not confirm the earlier reported higher cellular immune response of layers. Different significant relationships between physiological parameters in broilers and layers were found. Our results suggest that selection for enhanced growth does not necessarily affect specific immune competence of poultry.